Influence of manganese on apoptosis and glutathione content of cumulus cells during in vitro maturation in bovine oocytes - Anchordoquy, Juan Patricio (2014)
We have investigated the effect of different Mn concentrations on (1) DNA integrity of cumulus cells by olive tail moment (OTM); (2) cumulus cells apoptosis by Annexin V staining assay; (3) intracellular total glutathione (GSH-GSSG) content; and (4) oocyte nuclear maturation and embryo cleavage after in vitro fertilisation (IVF). For this purpose, 0 (control), 2 (Mn1), 5 (Mn2) and 6 ng/mL (Mn3) Mn concentrations were added to IVM medium. Comet assay analysed by OTM was significantly higher in cumulus cells arising from COCs matured without Mn (control, P < 0.01) respect to cumulus cells obtained from COCs matured with Mn (control: 5.18 2.3; Mn1: 2.93 2.2; Mn2: 2.63 2.4; Mn3: 2.92 2.4). The frequency of apoptotic cells was higher in the control group (control: 6.63 0.59; Mn1: 5.05 0.5; Mn2: 4.61 0.49; Mn3: 3.33 0.42). Intracellular concentration of GSH-GSSG increased in oocytes and cumulus cells matured in the presence of Mn (P < 0.01). There were no differences in percentages of nuclear maturation when Mn was added to IVM medium at any concentration, but at 6 ng/mL Mn a higher cleavage rate was observed respect to the control group (P < 0.05). In conclusion, deficiency in Mn concentration during in vitro maturation increased the damage in the DNA molecule and the frequency of apoptotic cumulus cells. However, the addition of an adequate Mn concentration (6 ng/mL Mn) to IVM medium improved the health of cumulus-oocyte complexes and produced more cleaved embryos 48 h after IVF.